Analisis Strategi Pemasaran Dalam Usaha Meningkatkan Penjualan Anyaman Purun Pada Brand Usaha Anyaba Di Marabahan - Husnul Khotimah; Hairul Hairul; Nurul Hasanah (JURNAL MANAJEMEN DAN BISNIS EKONOMI, 2023)
HUSNUL KHOTIMAH."Analysis of Marketing Strategy in an effort to increase sales of purun woven on the Anyaba business brand in Marabahan". Hairul Advisor, SE.M.M. and Nurul Hasanah, S.Sos., M.M The marketing strategy used to increase sales of purun woven at the Anyaba business brand in Marabahan is quite good, because it is able to market purun woven which was previously only considered a lower-middle class product to be promoted to the preferred class of millennials. The data collection technique used in this research is through Observation Method, Library (Library Research), Field Research (Field Research), Interview Method (Interview) and Documentation Method. This study uses qualitative data analysis, namely analysis based on opinions, thoughts and considerations that will describe and explain problems that are not described in numerical form. Based on the results of the study it can be concluded that: 1) The marketing strategy used woven Marabahan that has been carried out so far is to maintain product quality and continue to innovate to cooperate with related agencies or other parties with new products with attractive types, colors and packaging designs and changes according to market needs and the price offered is relatively cheaper because it targets young people who want to look trendy at a low cost and there are discounts on certain products on certain days to attract customers and 2) The marketing strategy that should be used in Anyaba Woven Marabahan to increase sales of its products, in addition to the ongoing strategy, it is necessary to add promotional aspects to buyers who have come to buy on the spot by giving discounts, from the aspect of the Anyaba Marabahan place which is located in a strategic location and is easy for buyers to visit but it is also necessary to think about adding new branches in other places such as the city of Banjarmasin and its surroundings